Augmenting innovation project portfolio management performance: the mediating effect of management perception and satisfaction. (2nd September 2014) - Spieth, Patrick; Lerch, Martin
<x xml:space="preserve">Abstract</x> Firms face the challenge of efficiently and effectively investing scarce resources in innovation projects in order to sustain or develop a firm's long‐term competitive advantage and sustainable growth. Innovation project portfolio management (IPPM) describes a firm's dynamic capability to assess the challenge of evaluating, selecting, and prioritizing innovation projects. The particular impacts of method usage, criteria usage, IPPM design, information availability, and internal interactions on management perception and satisfaction as well as on IPPM performance and innovativeness are hypothesized and tested. We found that methods and criteria play a negligible role in the IPPM context. IPPM design elements, like transparency and formality, are key drivers of high IPPM performance. Information availability is a key construct in driving IPPM performance, as well as management perception and satisfaction. Relevance of IPPM is supported by revealing IPPM performance's positive impact on firm performance, innovation project performance, and firm's innovativeness.